(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the natural and climatic conditions, soil cover, fertility status and degradation processes of the tillage lands of the Gallaorol district of the Jizzakh region of Uzbekistan. It is highlighted that the sharply continental climate of the region, seasonal and uneven distribution of precipitation directly affect the development of tillage farming. The problems arising from the water-physical properties of the soil, compaction, reduction of humus content, erosion processes and incorrect agrotechnical measures are assessed based on scientific sources and stationary experiments. The importance of effective agrotechnical measures aimed at maintaining soil fertility and increasing productivity is also substantiated